The Pagemaster - Kirschner, David, 1955-; Gertz, Paul.; Culkin, Macaulay, 1980-; Lloyd, Christopher, 1938-; Begley, Ed, Jr.; Casci, David A.; Contreras, Ernie; Johnston, Joe, 1950-; Hunt, Pixote; Joyce, Michael R.; Harris, Mel, 1957-; Goldberg, Whoopi, 1955-; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2002)
A tale of adventure and fantasy, which sends a young boy into the pages of the world's greatest stories. Seeking refuge from a storm, Richard Tyler enters an empty library only to be swept away into the magical animated world of The Pagemaster, where legendary characters from literary classics come alive.
Side A is widescreen; side B is standard.
Originally produced as motion picture in 1993.
Bonus features: featurette; Dream Away music video; theatrical trailers.
Music by James Horner.
Macaulay Culkin, Christopher Lloyd, Ed Begley, Jr., Mel Harris.
Voices: Whoopi Goldberg, Patrick Stewart, Leonard Nimoy, Frank Welker.
Keywords: Books and reading -- Drama; Libraries -- Drama; Fantasy films; Animated films; Video recordings for the hearing impaired; Feature films